THE ROLE OF THE EXTERNAL AUDITOR WHEN REVIEWING THE INTERNAL CONTROL SYSTEMS IN ELECTRONIC ACCOUNTING SYSTEMS (World Economics and Finance Bulletin, 2023)
This study aimed to explain the role of the external auditor when reviewing internal control systems in electronic accounting systems, given the importance of the effectiveness of the internal control system and its significant impact on the course of designing the external auditor's plan, and a statement of the possibility of relying on the outputs of the internal control system. The research aims to shed light on the importance of the scientific and practical qualification of the external auditor and the need to keep pace with technological developments and the importance of using technology in his work . The analytical descriptive approach was used to present the theoretical concepts related to the research, describe the research variables, and analyze the data and information to draw results that answer the research problem and try to generalize these results . The study concluded that the average rates for all axes were acceptable and within the medium and high limits, and the views of the respondents on the questionnaire were close.